Tax Incentives for Food Donations – a General Overview - Burzec, Marcin; Kowalewska, Ewa (Review of European and Comparative Law, 2022)
The study analyses tax law regulations in force in Poland and in selected European Union countries which may influence attitudes of entrepreneurs (taxpayers) in taking actions aimed at preventing food waste. This analysis demonstrates that all countries investigated in this study have made attempts to develop and implement various measures to combat the problem of food waste. At the same time, it is worth noting that properly constructed tax preferences are an important factor in preventing food waste, which is part of the sustainable development strategy implemented by European Union countries. In this respect, actions must be long-term and they should be based on various legal measures. Further changes in this area will be determined by some key factors. These include the need to use tax law regulations or to determine economic and social trends. Directions of activities of the state, local government and non-governmental organizations for counteracting food waste will also set course for these changes. Achieving sustainable development also at the stage of using food already produced should be based on optimization of all related processes, and thus also financial (mainly tax) processes. Therefore, attention should be paid in particular to the tax legislation in force in Poland and in selected European Union countries, i.e. the Act on tax on goods and services and the Act on corporate income tax.